Rehabilitation therapies for older clients of the Ontario home care system: Regional variation and client-level predictors of service provision - Armstrong, Joshua J.; Zhu, Mu; Hirdes, John P.; Stolee, Paul (Disability and Rehabilitation, 2015)
Purpose: To examine regional variation in service provision and identify the client characteristics associated with occupational therapy (OT) and physiotherapy (PT) services for older adults in the Ontario Home Care System. Methods: Secondary analyses of a provincial database containing comprehensive assessments (RAI-HC) linked with service utilization data from every older long-stay home care client in the system between 2005 and 2010 (n = 299 262). Hierarchical logistic regression models were used to model the dependent variables of OT and PT service use within 90 d of the initial assessment. Results: Regional differences accounted for 9% of the variation in PT service provision and 20% of OT service provision. After controlling for the differences across regions, the most powerful predictors of service provision were identified for both OT and PT. The most highly associated client characteristics related to PT service provision were hip fracture, impairments in activities of daily living/instrumental activities of daily living, cerebrovascular accidents, and cognitive impairment. For OT, hazards in the home environment was the most powerful predictor of future service provision. Conclusions: Where a client lived was an important determinant of service provision in Ontario, raising the possibility of inequities in access to rehabilitation services. Health care planners and policy makers should review current practices and make adjustments to meet the increasing and changing needs for rehabilitation therapies of the aging population.

Le vieillissement des francophones de l’Ontario. Livre blanc - Assemblée de la francophonie de l’Ontario (2019)

The health impact of living in a nursing home with a predominantly different spoken language - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes.1–3 Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services.4,5 French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones.6,7 However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored.

Quality and safety in long-term care in Ontario: The impact of language discordance - Batista, Ricardo; Prud'homme, Denis; Rhodes, Emily; Hsu, Amy; Talarico, Robert; Reaume, Michael; Guérin, Eva; Bouchard, Louise; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2021)
Objectives This study compared quality indicators across linguistic groups and sought to determine whether disparities are influenced by resident-facility language discordance in long-term care. Design Population-based retrospective cohort study using linked databases. Setting and Participants Retrospective cohort of newly admitted residents of long-term care facilities in Ontario, Canada, between 2010 and 2016 (N=47,727). Individual residents' information was obtained from the Resident Assessment Instrument Minimum Data Set (RAI-MDS) to determine resident's primary language, clinical characteristics, and health care indicators. Measures Main covariates of interest were primary language of the resident and predominant language of the long-term care facility, which was determined using the French designation status as defined in the French Language Services Act. Primary outcomes were a set of quality and safety indicators related to long-term care: worsening of depression, falls, moderate-severe pain, use of antipsychotic medication, and physical restraints. Multivariable logistic regression models were used to assess the impact of resident's primary language, facility language, and resident-facility language discordance on each quality indicator. Results Overall, there were few differences between francophones and anglophones for quality and safety indicators. Francophones were more likely to report pain (10.9% vs 9.9%; P = .001) and be physically restrained (7.3% vs 5.2%; P < .001), whereas a greater proportion of anglophones experienced worsening of depressive symptoms (24.0% vs 22.9%; P = .001). However, quality indicators were generally worse for francophones in Non-Designated facilities, except for pain, which was more commonly reported by francophones in French-Designated facilities. Anglophones were more likely to be physically restrained in French-Designated facilities (6.7% vs 5.1%; P < .001). Conclusions and Implications For francophones, quality indicators tended to be worse in the presence of resident-facility language discordance. However, these findings did not persist after adjusting for individual- and facility-level characteristics, suggesting that the disparities observed at the population level cannot be attributed to linguistic factors alone.

Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.

Activité physique, santé et vieillissement chez des femmes francophones de l'Ontario - Beausoleil, Nathalie; Martin, Geneviève (La Revue canadienne du vieillissement, 2002)
Cet article fait état d'une recherche qualitative réalisée en milieu francophone minoritaire ontarien. Les perceptions et les pratiques de l'activité physique d'une trentaine de femmes sont analysées en regard de fondements sociologiques et de discours actuels sur le vieillissement. Ces discours portent sur la responsabilité individuelle de la santé, sur les liens entre la santé, la beauté et le vieillissement, sur la pratique des sports, la masculinité et la féminité et enfin sur l'obligation de l'activité physique à tous les cycles de vie. Les résultats de l'étude auprès de femmes regroupées en trois tranches d'Çge permettent de réaliser que si ces femmes ont adopté le discours de la responsabilité individuelle pour la santé et la prévention des effets néfastes du vieillissement par l'exercice physique régulier, elles peuvent aussi etre vues comme des sujets trouvant dans leur vie quotidienne des stratégies pour ne pas subir les pressions des normes de santé et de beauté liées au vieillissement, pour faire face aux contraintes et pour développer une façon saine de vivre le vieillissement.

L’offre active et l’accessibilité des services sociaux et de santé chez les personnes atteintes de démence en contexte francophone minoritaire - Bélair, Josée (Université d'Ottawa, 2019)
À l’heure actuelle, les besoins de soins de santé augmentent en réponse à la démographie vieillissante (Organisation mondiale de la santé, 2018). Pourtant, la difficulté d’accès aux services sociaux et de santé chez les usagers en situation minoritaire est une réalité présentée à l’aide de la littérature scientifique. En ce qui a trait aux populations minoritaires de la ville d’Ottawa, les études antérieures permettent de démontrer les obstacles touchant plus particulièrement les personnes francophones dans l’accessibilité des services sociaux et de santé (Kubina et collab., 2018). Dans le contexte de cette étude qualitative, le diagnostic de démence est pris en compte en tant que facteur explicatif de la difficulté accrue vécue chez les aînés francophones dans le recours aux services sociaux et de santé (Carbonneau et Drolet, 2014b). Un total de cinq proches aidants de la ville d’Ottawa a été recruté dans le but d’alimenter les objectifs de la recherche, c’est-à-dire : 1) d’identifier les barrières linguistiques dans la trajectoire des services sociaux et de santé ; 2) d’identifier l’influence des structures du Cadre d’analyse des leviers d’action pour l’accès et l’intégration des services sociaux et de santé pour les communautés de langue officielle en situation minoritaire (CALA) (Savard et collab., 2017) (Voir figure 1) dans l’accès aux services sociaux et de santé chez la population à l’étude. Quoique la majorité des participants à la recherche aient exprimé leur satisfaction par rapport aux services en français reçus pour leur proche atteint d’une démence, certaines barrières linguistiques telles que le manque de continuité dans les services en français ont été identifiées ainsi que le manque d’information quant à la disponibilité des services dans la communauté. De plus, la majorité des participants à la recherche ont pu identifier au moins un moment où les services à leur disponibilité étaient strictement en anglais. Bref, parmi les cinq proches aidants interviewés, quatre ont mentionné la nécessité de lutter pour l’obtention des services en français.

Étude sur les populations âgées et l’accès aux soins de longue durée en français en Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)
Ce rapport présente une analyse de la demande et de l’offre de services de santé en français (SSF) dans le secteur des soins de longue durée (SLD) en Ontario. En nous appuyant sur des données publiques ainsi que sur des données administratives fournies par le ministère de la Santé de l’Ontario, le rapport examine : 1. la demande régionale de SSF, évaluée selon la population ontarienne âgée de 65 ans et plus et la population francophone de ce groupe d’âge ; 2. l’offre de SSF, mesurée par le nombre et le type de foyers présents dans chaque région, ainsi que par les compétences linguistiques en français de leur personnel.

Study of aging populations and access to French-language long-term care in Ontario - Belanger, Christopher; Timony, Patrick; Glaude, Normand; Bouchard, Louise (Université d'Ottawa, 2024)

Do chronically ill, elderly Francophone patients believe they are adequately served by Ontario’s health care system? Exploratory study of the effect of minority-language communities - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Canadian Family Physician, 2012)

Impact de la situation linguistique minoritaire sur les soins de santé pour des personnes âgées francophones de l'Ontario souffrant de maladies chroniques : une étude qualitative exploratoire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Consortium national de formation en santé, 2010)

Les Franco-Ontariens âgés souffrant de maladies chroniques se perçoivent-ils bien desservis ? Une étude exploratoire de l'impact de la situation linguistique minoritaire - Bouchard, Louise; Chomienne, Marie-Hélène; Benoit, Monique; Boudreau, Françoise; Lemonde, Manon; Dufour, Suzanne (Le médecin de famille canadien, 2012)

La santé des personnes âgées francophones vivant en situation minoritaire au Canada : enjeux et besoins - Bouchard, Louise; Desmeules, Martin (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé L’objectif de ce chapitre est de présenter le profil sociodémographique et sanitaire de la population aînée francophone (65 ans et plus) vivant en situation linguistique minoritaire afin d’en ressortir les enjeux et les besoins qui la caractérisent. Nous aborderons dans un premier temps le fait minoritaire et son effet potentiel sur le vieillissement de la population et la position sociale des personnes âgées, leur santé et leur accès aux services. Une seconde section établira, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes (ESCC, cycles combinés, 2003-2012), le portrait sociosanitaire des aînés en fonction de trois grandes régions canadiennes (les provinces de l’Atlantique, l’Ontario et les provinces de l’Ouest). Enfin, nous discuterons ici de deux enjeux qui nous apparaissent fondamentaux au regard de cette population minoritaire, soit celui de la littératie en santé, c’est-à-dire la capacité de communiquer et de naviguer adéquatement dans le système de santé, et celui de l’offre active de services, une mesure d’équité et de qualité des soins. Mots-clés : aînés francophones, minorités linguistiques, portrait sociosanitaire, Canada, Enquête sur la santé dans les collectivités canadiennes (ESCC).

The health of Francophone seniors living in minority communities in Canada: Issues and needs - Bouchard, Louise; Desmeules, Martin (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Francophone seniors in Ontario: A health portrait - Bouchard, Louise; Makvandi, E.; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa, 2014)

Les aînés francophones de l’Ontario : un portrait de santé. - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

The health of the Francophone population aged 65 and over in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Comment améliorer la santé des aînés francophones vieillissant en Ontario ? Entre approche populationnelle et santé communautaire - Bouchard, Louise; van Kemenade, Solange (La santé communautaire en 4 actes : repères, acteurs, démarches et défis, 2016)

La santé des aînés francophones en situation linguistique minoritaire : états des lieux en Ontario - Bourbonnais, Valérie (Université d’Ottawa, 2007)
L'objectif de cette thèse est de tracer les profils comparatifs des états de santé des populations francophones et anglophones âgées de 65 ans et plus de l'Ontario en utilisant les données de l'Enquête sur la santé et les collectivités canadiennes (ESCC) recensées par Statistique Canada. Dans un deuxième temps, ces profils seront également analysés en fonction du genre. Or, trois grands volets seront examinés dans ce projet: (1) les caractéristiques socio-démographiques, (2) les états de santé déclarés et perçus, (3) ainsi que l'utilisation et la satisfaction à l'égard des services de soins de santé. L'objectif principal de cette thèse est de démontrer que le fait de vivre dans un contexte linguistique minoritaire engendre des facteurs risquant d'influencer négativement le vieillissement de la minorité sociolinguistique francophone de l'Ontario. En puisant à la discipline sociologique, une théorisation de la minorité sera utilisée afin d'appuyer la thèse avancée. Globalement les analyses révèlent un profil socioéconomique et un profil de santé plus précaires chez les aînés de la minorité francophone comparativement aux aînés de la majorité anglophone. Il est intéressant de noter que cette précarité de la santé s'exprime autant chez les hommes que chez les femmes de la minorité francophone, malgré que celle-ci s'articule différemment pour certaines variables. Quant à la prestation des services de soins de santé, les aînés de la minorité francophone sont unanimement insatisfaits de l'accessibilité, ainsi que de la qualité des services dans l'ensemble de la province ontarienne.

La trajectoire des services sociaux et de santé d’aînés atteints d’une démence vivant en contexte francophone minoritaire : un engagement de multiples piliers durant une navigation complexe - Carbonneau, Corine; Drolet, Marie (Reflets, 2014)

Les francophones de l'Ontario de 65 ans et plus : un profil statistique - Cardinal, Linda; Plante, Nathalie; Sauvé, Anik (Chaire de recherche sur la francophonie et les politiques publiques et Université d'Ottawa, 2006)

Coup d’œil sur la recherche : Qualité et sécurité des soins de longue durée en Ontario [infographie] - Consortium national de formation en santé; van Kemenade, Solange (2022)

Management strategies to improve French language service coordination and continuity for official language Francophone seniors in Canada - de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Kubina, Lucy-Ann (Healthcare Management Forum, 2020)
Evidence suggests that language barriers present obstacles to healthcare access and quality for Francophone seniors in official language minority communities across Canada. Addressing language barriers and providing continuity is challenging, as French language services (FLSs) rely heavily on bilingual providers and the practice of active offer by all staff. This qualitative research used semi-structured group and individual interviews to explore mechanisms supporting FLS coordination and continuity in two Canadian provinces. Identification of the language variable in health records, virtual healthcare, and FLS directories are conducive to FLS continuity, but financial and resource limitations present major obstacles. Management strategies to facilitate continuity of FLS across health organizations are discussed.

Le recrutement et la rétention des professionnels de la santé et des services sociaux bilingues en situation minoritaire - de Moissac, Danielle; Savard, Sébastien; Ba, Halimatou; Zellama, Faïçal; Benoît, Josée; Giasson, Florette; Drolet, Marie (Université de Saint-Boniface et Université d'Ottawa, 2014)
Cete étude cherchait à connaitre les éléments favorisant l’engagement et la motivation des professionnels ainsi que les pratiques de gestion des ressources humaines qui encourage le personnel bilingue à s’intéresser au travail en milieu bilingue et à demeurer en poste.

Agir pour avoir accès à des services sociaux et de santé en français. Des francophones en situation minoritaire nous enseignent quoi faire! - Drolet, Marie; Arcand, Isabelle; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée (Revue canadienne de service social, 2015)
Même si les droits des francophones de l’Ontario sont garantis par la Loi de 1986 sur les services en français, l’accès à des services sociaux et de santé en français dans cette province s’avère complexe en raison d’importantes barrières à recevoir de tels services sur un continuum. Nous avons exploré à l’aide d’entrevues qualitatives les points de vue de 40 parents et proches aidants francophones qui vivent en contexte bilingue dans la région d’Ottawa et dont l’enfant ou l’aîné pour lequel ils ont une responsabilité d’aidant utilise des services sociaux et de santé en français. Ces francophones s’avèrent des acteurs au sein de leur trajectoire de services, adoptant cinq stratégies pour accéder à de tels services. De plus, le sentiment de confort et la relation de confiance que procure l’usage du français tout au long de l’intervention, ainsi que le soutien des professionnels francophones ont facilité leur démarche. Il n’en demeure pas moins que l’offre de services en français ne doit pas devenir la responsabilité d’individus ou d’une minorité. Mots-clés : Francophonie en situation minoritaire, accès à des services sociaux, minorité linguistique, barrières aux services, offre active de services en français, entrevues qualitatives

Health services for linguistic minorities in a bilingual setting: Challenges for bilingual professionals - Drolet, Marie; Savard, Jacinthe; Benoît, Josée; Arcand, Isabelle; Savard, Sébastien; Lagacé, Josée; Lauzon, S.; Dubouloz, Claire-Jehanne (Qualitative Health Research, 2014)
We explore in this qualitative research the challenges faced by bilingual health and social services professionals in a Canadian bilingual setting, as well as the strategies used to overcome them. Eight focus groups were conducted with a total of 43 bilingual Francophone professionals who offered services in French in 21 health and social service organizations in eastern Ontario, Canada. We highlight linguistic issues affecting a minority Francophone clientele, the shortage of services in French, and organizational issues within these agencies. The solutions that the professionals adopt for better serving the clients and overcoming these challenges focus on adapting services from linguistic angles. In the long term, such an enhanced approach can affect staff well-being. Ensuring access to services for linguistic minority populations and the active offer of same should not rest solely on the shoulders of such professionals, but rather on organizational strategies.

L’expérience des francophones dans l’Est ontarien : importance des personnes pivots (usagers et intervenants) et influence des structures encadrant le système de santé et des services sociaux - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Le présent chapitre décrit l’expérience d’accès à des services sociaux et de santé en français de francophones de l’Est ontarien. Les expériences et les perspectives de 40 parents, aînés et proches aidants ont été recueillies à l’aide d’entrevues semi-structurées. Une analyse qualitative des verbatim ainsi qu’une analyse visuelle des trajectoires d’un sous-groupe de neuf participants ont permis de faire ressortir les facilitateurs et les défis d’accès aux services en français rencontrés par ces usagers, à partir de leur perspective ou de celle de leur proche aidant. Plus spécifiquement, ce chapitre met l’accent sur les éléments facilitateurs dans le but d’en tirer des leçons pour améliorer les services sociaux et de santé en langue officielle en situation minoritaire. Mots-clés : accès aux services en français, francophones Ontario, recherche qualitative.

The experience of Francophones in Eastern Ontario: The importance of key facilitators (service users and providers) and the influence of structures supporting the health and social services system - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Comprendre l’expérience des femmes âgées en matière de l’accessibilité aux services sociaux et de santé en contexte francophone minoritaire [mémoire de maîtrise, Université d'Ottawa] - Dubuc, Vanessa (Université d'Ottawa, 2019)
Au Canada, les francophones en contexte minoritaire demeurent contraints au niveau de l’accès aux services sociaux et de santé en français en raison de barrières linguistiques. De plus, les femmes âgées en contexte francophone minoritaire sont sujettes aux inégalités vécues par les femmes âgées de façon générale, mais subissent également de la discrimination liée à leur statut de minorité. La présente recherche s’intéresse à l’expérience des femmes âgées en contexte francophone minoritaire en matière d’accessibilité aux services sociaux et de santé. De manière plus précise, cette recherche a pour but : 1) d’identifier les facilitateurs et les défis rencontrés par ces femmes ; 2) de comprendre la manière dont ces facilitateurs et ces défis ont des effets sur les différentes sphères de leur vie ; 3) examiner l’effet des structures institutionnelles et organisationnelles quant à l’accessibilité aux services sociaux et de santé de celles-ci. Afin de recueillir nos données, des entrevues semi-structurées ont été effectuées auprès de quatre participantes. L’analyse thématique des données, suivant un cadre théorique féministe intersectionnel, permet de mettre en évidence les éléments suivants selon les expériences des participantes : 1) l’accès aux services sociaux et de santé en contexte francophone minoritaire ; 2) la question du genre ; et 3) les réalités structurelles. Concrètement, les résultats indiquent que les participantes ont de la difficulté à accéder à des services sociaux et de santé dans leur langue, mais que le fait de s’identifier comme une femme ne semble pas jouer un rôle déterminant dans leur accès aux services en français. À la lumière des résultats, des recommandations sont proposées afin de mieux répondre aux besoins des groupes en situation linguistique minoritaire. Mots clés : francophone minoritaire, femme âgée, accès aux services sociaux et de santé, féminisme intersectionnel

Initiatives intergénérationnelles en santé. Rapport final - Duguay, Benoît (La Commission nationale des parents francophones, la Fédération des aînées et aînés francophones du Canada et la Société Santé en français, 2007)

La prise en compte de la langue dans les foyers de soins pour personnes âgées - Forgues, Éric; Gaucher, Charles; Guignard Noël, Josée; Kabano, John; Michaud, Jacques (Institut canadien de recherche sur les minorités linguistiques, 2012)

Vieillir en situation linguistique minoritaire au Canada et ses implications pour la santé [infographie] - Gagnon-Arpin, Isabelle; Bouchard, Louise; Gaboury, Isabelle; Bourbonnais, V.; Chomienne, Marie-Hélène (2009)

The pathway to diagnosis of dementia for Francophones living in a minority situation - Garcia, Linda J.; McCLeary, L.ynn; Emerson, Victor; Léopoldoff, Hélène; Dalziel, William; Drummond, Neil; Cohen, Carole; Koehn, Sharon; Silvius, James (The Gerontologist, 2014)
Purpose of the Study: As the prevalence of dementia increases, the pressure to make early diagnoses also increases. Although patients must be able to identify the symptoms to access appropriate services, they may not be equally accessible to all citizens in a multicultural society. Health care professionals and patients may lack a common “first language.” This study explores the experience of francophone persons with dementia (PWD) and their caregivers during the peri-diagnostic period. Design and Methods: Individual interviews were undertaken to elicit information regarding symptoms, the role of the family and friends, and the access to formal services. Seven PWD and their caregivers who spoke French as their primary language but who lived in a primarily English-speaking region completed the interviews. Results and Implications: No single symptom seemed sufficient to alert participants that dementia might be present. Participants communicated that there was a dire need to inform the public about the signs of dementia; they spoke of the role of the family physician and the importance of having a long-standing relationship with a health professional. For some, having similar personal characteristics, such as language and culture, might accentuate the strength of the relationship and facilitate the process of diagnosis.

Access to dementia services in a minority situation: The case of Francophones in Ontario [infographic] - Garcia, Linda; Chomienne, Marie-Hélène; Cadieux, M.-A.; Farmanova, E.; McCleary, L.; Molnar, F.; Agapitos, M.; Dalziel, W.; Khoury, L.; French-Merkley, V.; Joanisse, J. (2014)

Does end-of-life care differ for Anglophones and Francophones? A retrospective cohort study of decedents in Ontario, Canada - Guerin, Ewa; Batista, Ricardo; Hsu, Amy. T.; Gratton, Valérie; Chalifoux, Mathieu; Prud’homme, Denis; Tanuseputro, Peter (Journal of Palliative Medicine, 2018)
Background: Approximately half of decedents in Ontario, Canada, receive some palliative care, but little is known about the influence of language on the nature of these services. Objective: To examine differences between English- and French-speaking residents of Ontario in end-of-life care and outcomes (e.g., health care costs and location of death). Design: A retrospective cohort study using multiple linked databases. Setting/Subjects: A population-based cohort of decedents in Ontario (2010–2013) who were living in long-term care institutions (i.e., nursing homes) or receiving home care before death (N = 25,759). Data from two regions with higher representations of Francophones were examined, with the final distribution by primary language being 75% Anglophone, 18% Francophone, and 7% other languages. Results: Compared with Anglophones, Francophones were more frequent users of long-term care (47.6% vs. 37.1%) and less frequent users of home care (71.3% vs. 76.3%). In adjusted models, the number of days spent in hospital in the last 90 days of life was similar between Anglophones and Francophones, although the odds of dying in hospital were significantly higher among the latter. The mean total health care cost in the last year of life was slightly lower among French ($62,085) compared with English ($63,814) speakers. Conclusions: There are statistically significant differences in end-of-life outcomes between linguistic groups in Ontario, namely more institutionalization in long-term care, less home care use and more deaths in-hospital among Francophones (adjusted). Future research is needed to examine the cause of these differences. Strategies to ensure equitable access to quality end-of-life care are required.

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire à domicile (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2024)

Récit d’une proche aidante francophone durant la pandémie de la COVID-19 : personne bénéficiaire en maison de retraite (infographie) - Hatungimana, Nelly Oriane; Benoît, Josée; Savard, Jacinthe; Savard, Sébastien (2024)

Protocole d’évaluation de la sécurité à domicile (PESAD) : version francophone du SAFER-HOME v.3 - Hébert, Michèle; Brasset-Latulippe, Anne; Bourgault-Côté, Sylvianne; Meilleur, Valérie; Chiu, Teresa (Francophonies d'Amérique, 2009)
Les intervenants de la santé sont appelés à se prononcer sur la sécurité des aînés vivant à domicile et ils ont, à cet effet, très peu d’outils francophones à leur disposition. Le Protocole d’évaluation de la sécurité à domicile (PESAD) est issu de la traduction et de la validation transculturelle du SAFER-HOME. Le processus de validation et l’étude de la fidélité des résultats ont mis en lumière un outil intéressant et possédant de bonnes qualités métrologiques. Il permet aux intervenants francophones d’obtenir des résultats d’évaluation complets et rigoureux relativement à la sécurité à domicile des aînés francophones.

Les bienfaits de la socialisation au programme de jour du Centre de services Guigues (CSG) sur la santé des personnes âges francophones ayant vécu l'isolement ou la solitude dans la région d'Ottawa - Kajuka, Dale (Université Laurentienne, 2017)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Health and social services for Francophone seniors in Eastern Ontario and Manitoba: Guidelines to improve the continuity of French language services. Research Report - Summary. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (Grefops), 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les services sociaux et de santé pour les personnes âgées francophones de l’Est ontarien et du Manitoba : lignes directrices pour améliorer la continuité des services en français. Rapport de recherche - Résumé. - Kubina, Lucy-Ann; de Moissac, Danielle; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette (Groupe de recherche sur la formation professionnelle en santé et service social en contexte francophone minoritaire, 2018)

Les trajectoires d'aînés dans le contexte de l'accès à des services sociaux et de santé en français dans la région d'Ottawa - Kubina, Lucy-Ann; Savard, Jacinthe; Drolet, Marie; Savard, Sébastien; Benoît, Josée (Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire, 2018)

La première étape de la validation transculturelle des versions anglophones des tests de l'horloge et du Mini-Mental pour mesurer les capacités cognitives des Franco-Ontariens âgés de plus de 65 ans - Larocque, Sylvie; Lavoie, Anne-Marise; Omri, Nadia (Reflets, 2021)
La maladie d’Alzheimer est un syndrome neurodégénératif chronique caractérisé par un déclin cognitif et mnésique. Les personnes atteintes par cette maladie développent des affections rattachées à la langue. Il est important de faire passer des tests de dépistage dans la langue maternelle de la personne puisque l’aptitude linguistique décline avec la progression de la maladie. De manière générale, le Mini-mental et le test de l’horloge sont administrés en anglais aux francophones du nord de l’Ontario ce qui peut mener à une sous-évaluation de leurs capacités cognitives et à un diagnostic erroné. Voilà pourquoi le but de cette recherche était de développer et valider les tests psychométriques francophones administrés aux Franco-Ontariens. Le Mini-mental et le test de l’horloge ont été traduits selon la validation transculturelle de Caron (1999) et testés auprès des francophones du Grand Sudbury qui souffraient de déficits cognitifs (N=14). Aucune différence statistique (p>.05) entre les scores de la traduction franco-ontarienne du test de l’horloge et du Mini-mental comparés aux tests originaux n’a été détectée. Bien que d’autres recherches soient nécessaires, selon les auteures, ces traductions permettront d’assurer un dépistage juste de cette maladie chez les francophones âgés en situation minoritaire. Mots-clés : dépistage d’Alzheimer, Mini-mental de Folstein, test de l’horloge, traduction transculturelle

Exploring Primary Care Physicians’ Experiences of Language and Cultural Discordant Care for Linguistic Minority Patients at the End-of-Life: A Study Protocol - Lee, Seung Heyck; Gibb, Maya; Karunananthan, Sathya; Cody, Margaret; Tanuseputro, Peter; Johnston, Sharon; Kendall, Claire; Bedard, Daniel; Collin, Stéphanie; Kehoe MacLeod, Krystal (International Journal of Qualitative Methods, 2023)
Health disparities exist across different linguistic groups. Language barriers in primary care can negatively affect access to healthcare services and the quality and safety of care at the end-of-life. This study will take a novel, in-depth look at the experience of language- and/or cultural-discordant care for adults from linguistic minority groups through the eyes of primary care physicians providing palliative and/or end-of-life care. Language and cultural discordance means that the physician and patient do not speak the same language or are not from the same cultural background. Qualitative data from primary care physicians (n = 12–24) providing language-discordant end-of-life care to Francophone and/or Allophone older adults across different care models and diverse geographies in Ontario will be collected through semi-structured interviews. Reflexive thematic analysis will be used to report themes within the data and consider the influence of the social locations of the researcher and research participants, geographic considerations impacting service provision, and barriers imposed by differing primary care funding structures on the provision of palliative and end-of-life care for linguistic and cultural minority groups in Ontario. Findings from this study will identify the interconnections among language and cultural discordance, care model, geographic region, and physician perceptions of their combined effects on access to, and quality of, palliative and end-of-life care. This evidence will be key to informing clinical practice guidelines and mobilizing change to improve primary care access and quality for adults at the end-of-life from linguistic and cultural minority populations across Ontario. Keywords: language discordance, qualitative research, reflexive thematic analysis, palliative care, primary care physicians, semi-structured interviews

Impact de la situation linguistique minoritaire sur les soins de santé pour les personnes âgées francophones de l’Ontario souffrant de maladies chroniques : partage des connaissances et rétroaction. Rapport de recherche - Lemonde, Manon; Boudreau, Françoise; Dufour, Suzanne (Réseau de recherche appliquée sur la santé des francophones de l’Ontario, 2012)

Déterminants socio-économiques affectant le choix d’une maison de retraite : points de vue des résidents d’une maison francophone à Toronto [thèse de maîtrise, Université Laurentienne] - Maïna, Ali (2013)
Cette étude vise à explorer le problème de logement lié au vieillissement de la population. L’objet principal de la présente thèse est de comprendre les déterminants socioéconomiques qui influencent la décision des personnes âgées d’aller vivre en maison de retraite et leur choix d’une maison de retraite en particulier. Les données ont été collectées à l’aide d’une méthode qualitative, par l’entremise d’entrevues semi-directives. Les trente-sept personnes âgées constituant notre échantillon se sont exprimées sur leurs expériences afin de nous permettre de mieux cerner les déterminants socio-économiques affectant leur choix d’aller vivre en maison de retraite. Tous nos participants sont des résidents de la maison Héritage, une institution de Toronto. Les résultats de cette recherche nous révèlent que le choix d’aller vivre dans une maison comme l’Héritage implique des aspects qui dépassent largement les motifs purement économiques. En conséquence, les déterminants liés à la solitude, aux décès de conjoint (e), au soutien adapté, ont été très influents dans la première phase du choix d’aller vivre dans une maison de retraite. En revanche, dans le choix de l’Héritage, des déterminants liés à l’identité, comme la langue, les valeurs culturelles, ont été plus influents. Mots-clés déterminants socio-économiques, personnes âgées, maison de retraite, maison francophone (Héritage), langue, valeurs culturelles, financier

Maintien à domicile francophone - Martel, Richard; Pinsonneault, Carole (Reflets, 1996)

L'état de santé des personnes âgées francophones en Ontario - McKellar, Jocelyne (Reflets, 1999)

Accès aux soins de longue durée dans la région d'Érié St. clair : Analyse et recommandation - Mian, Guy (Entité de planification des services de santé en français Érié St.Clair/Sud-Ouest, 2021)
Ce rapport a été préparé dans le cadre du Plan d’Action Conjoint 2019-2022 du RLISS-Entité,¹ où les soins et les services aux aînés sont considérés comme prioritaires et, en particulier, l’accès aux soins de longue durée (SLD) dans la région d’Érié St. Clair. Le présent rapport vise à formuler des recommandations à l’intention de Santé Ontario (SO) Ouest afin de combler les lacunes en matière d’accessibilité aux soins de longue durée (SLD) en français et, par conséquent, dans les services de soutien à domicile et en milieu communautaires (SSDMC) afin de maintenir les aînés francophones à domicile dans la région d’Érié St. Clair (ESC). Dans la mesure du possible, le rapport proposera également des recommandations pour la localité de London dans la région du Sud-Ouest (S-O).

La prise en compte du français dans l’organisation des services en foyers de soins majoritairement anglophones au Canada - Michaud, Jacques; Forgues, Éric; Guignard Noël, Josée (Minorités linguistiques et société, 2015)
L’accès aux services de santé en français préoccupe grandement les communautés francophones vivant en situation minoritaire. Le présent article offre un survol de l’espace francophone dans les résidences collectives d’aînés du Nouveau-Brunswick, de la Nouvelle-Écosse et de l’Ontario à la lumière d’une recherche exploratoire menée en 2012. L’analyse des données obtenues auprès d’aînés, d’aidants et du personnel, l’examen de la répartition géographique des résidences et de la population d’aînés francophones, ainsi qu’un aperçu du contexte réglementaire encadrant le fonctionnement de ces résidences permettent de définir la problématique pertinente. Des actions en vue d’améliorer la situation sont examinées. Mots-clés : espace francophone, services de santé en français, francophones en situation minoritaire, foyers de soins, résidences collectives, vieillissement de la population

Enabling the participation of marginalized populations: Case studies from a health service organization in Ontario, Canada - Montesanti, Stephanie. R.; Abelson, Julia; Lavis, John. N.; Dunn, James. R. (Health Promotion International, 2017)
We examined efforts to engage marginalized populations in Ontario Community Health Centers (CHCs), which are primary health care organizations serving 74 high-risk communities. Qualitative case studies of community participation in four Ontario CHCs were carried out through key informant interviews with CHC staff to identify: (i) the approaches, strategies and methods used in participation initiatives aimed specifically at engaging marginalized populations in the planning of and decision making for health services; and (ii) the challenges and enablers for engaging these populations. The marginalized populations involved in the community participation initiatives studied included Low-German Speaking Mennonites in a rural town, newcomer immigrants and refugees in an urban downtown city, immigrant and francophone seniors in an inner city and refugee women in an inner city. Our analysis revealed that enabling the participation of marginalized populations requires CHCs to attend to the barriers experienced by marginalized populations that constrain their participation. Key informants outlined the features of a ‘community development approach’ that they rely on to address the barriers to marginalized peoples' involvement by strengthening their skills, abilities and leadership in capacity-building activities. The community development approach also shaped the participation methods that were used in the engagement process of CHCs. However, key informants also described the challenges of applying this approach, influenced by the cultural values of some groups, which shaped their willingness and motivation to participate. This study provides further insight into the approach, strategies and methods used in the engagement process to enable the participation of marginalized populations, which may be transferable to other health services settings.

Vers des services attirants, accessibles et pertinents pour les personnes âgées immigrantes francophones ? - Nduwimana, Mathilde; Home, A. (Reflets, 1995)
Cet article décrit et analyse les besoins et préoccupations des personnes âgées autonomes appartenant aux groupes ethniques francophones et résidant dans Ottawa-Carleton. L'objectif principal est d'explorer les raisons pour lesquelles elles utilisent peu les services de soutien communautaires pour les personnes âgées francophones. Nous avons effectué des entrevues semi-structurées auprès de quatre représentantes et de six personnes âgées des communautés ethno-culturelles francophones, et nous avons effectué une analyse de contenu par thème. Les répondantes ont souligné les besoins de contacts sociaux, d'apprentissage du français et/ou de l'anglais, d'accès aux moyens financiers adéquats et d'information sur les ressources disponibles. Des obstacles liés au contexte socio-écono-politique dans la société d'accueil entravent la satisfaction de ces besoins. La levée de certaines barrières concrètes, la modification des politiques sociales et des pratiques d'intervention faciliteraient l'accès aux services par les personnes âgées des groupes ethniques francophones et augmenteraient leurs options.

Reach, adoption, and implementation strategies of a telehealth falls prevention program: perspectives from francophone communities across Canada. - O’Neil, Jennifer; Dionne, Nathalie; Marchand, Sylvie; Cardinal, Dominique; Handrigan, Grant; Savard, Jacinthe (Health Promotion and Practice, 2024)
Introduction. A fall may impact a person’s physical, emotional, and psychological well-being. Fall prevention programs are being implemented to reduce these negative outcomes. However, linguistic barriers in health services may reduce access to such prevention programs. A telehealth fall prevention program was designed to increase access to such programs in French for Francophone minority communities in Canada. This capacity-building project aimed to support community partners to deliver this telehealth program and document strategies used to reach, adopt, and implement the program within various Francophone and Acadian Minority Communities. Methods. A sequential explanatory mixed methodology was used to document reach, adoption, and implementation strategies and describe the lived experiences of program facilitators and organization representatives. Reach, adoption, and implementation were documented and analyzed descriptively, while lived experiences were analyzed using content analysis following the Consortium Framework for Implementation Research. Results. Twelve organization representatives or program facilitators from eight organizations operating in four different provinces participated in the study. Three themes emerged from the qualitative data on reach and adoption: external context, internal context, and capacity building. Four themes were identified as barriers and facilitators to implementation: level of preparation and time management, interpersonal relations and telepresence, exercise facilitation and safety, and technological problem-solving. Conclusion. Using tailored reach and adoption strategies such as prioritizing provinces with higher proportions of needs and training local community program facilitators may lead to the successful implementation of a new telehealth fall prevention program. Results from this study could potentially inform other primary prevention programs or telehealth program implementation.

Deux projets innovateurs destinés aux aînés francophones d’Ottawa-Carleton - Ouellet, Rachelle (Reflets, 1996)
Cet article décrit deux projets innovateurs destinés aux aînés francophones d’Ottawa-Carleton: 1) le Programme pour les aînés francophones des communautés ethno-culturelles élaboré par l'Assemblée des affaires francophones du Conseil sur le vieillisement d'Ottawa-Carleton et mis sur pied au sein des trois centres pour aînés francophones de la région. 2) le Projet pilote «Vieillir chez soi», un modèle élaboré en vue de coor donner les services sociaux et de santé fournis aux résidents des logements pour personnes âgées de Logement Ottawa-Carleton et dont certaines composantes ont été mise à l'essai dans trois immeubles de logements pour personnes âgées d'Ottawa-Carleton.

Aînés francophones et intervenants multiethniques en santé : un projet de formation interculturelle adapté aux collègues francophones canadiens - Parent, R.; Bouchard, Louise; Lebel, M. (Reflets, 2014)

Le Programme régional des soins palliatifs de Sudbury : une réussite à souligner et à protéger - Racine, Guy (Reflets, 1999)
Parmi les programmes et les services de santé offerts à la population de la région de Sudbury, il en est un qui mérite une mention particulière tant par l’efficacité de son organisation que par la qualité du « caring » qu’on y exerce et c’est le Programme régional des soins palliatifs.

Linguistic factors and COVID-19 outcomes among long-term care residents in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Imsirovic, Haris; Bjerre, Lise; Kendall, Claire E.; Bouchard, Louise; Gauthier, Alain P.; Landry, Josette-Renée; Chomienne, Marie-Hélène; Muray, Mwali; Hsu, Amy; Prud'homme, Denis; et al. (BMC Geriarics, 2025)
Abstract Background The COVID-19 pandemic disproportionately affected frail individuals, especially those living in long-term care (LTC) homes. This study examined the role of linguistic factors on COVID-19 related outcomes in LTC homes. Methods We performed a population-based, retrospective cohort study of residents living in LTC homes in Ontario, Canada who were diagnosed with COVID-19 between March 31, 2020 and March 31, 2021. Resident language, obtained from LTC assessments, was used to classify residents into one of the three linguistic groups: Anglophone (English), Francophone (French), and allophone (other language). Language of the LTC home was determined using a person-time representation of the languages spoken by residents within each LTC home. We defined LTC facilities as French homes when Francophone residents contributed more than 25% of the person-days, and allophone homes when allophone residents contributed more than 50% of the person-days. Residents whose language corresponded to the language of the LTC home in which they were living were said to have received language-concordant care, while all other residents were said to have received language-discordant care. The outcomes of this study were ED visits, hospitalizations, and mortality within 90 days. Results We included a total of 26,829 LTC residents (20,315 Anglophones, 1,032 Francophones, and 5,482 allophones) living in 572 LTC homes (502 English, 28 French, 42 allophone) who were diagnosed with COVID-19. LTC residents who lived in language-discordant homes were more likely to have ED visits (adjusted HR 1.12, 95% CI 1.01–1.25) and hospitalizations (adjusted HR 1.15, 95% CI 1.02–1.29) when compared to LTC residents who lived in language-concordant homes. Residents-facility language discordance was not associated with overall mortality (adjusted HR 1.00, 95% CI 0.91–1.10) or in hospital mortality (adjusted HR 1.04, 95% CI 0.88–1.23). Conclusion Residents living in language-discordant LTC facilities experienced more ED visits and hospitalizations following diagnosis of COVID-19. The findings of this study highlight the importance of providing frail, vulnerable individuals with linguistically concordant care.

Qualité et sécurité des services de santé offerts en situation linguistique minoritaire en Ontario : investigations des données administratives de santé. - Reaume, Michael; Batista, Ricardo; Prud’homme, Denis; Tanuseputro, Peter (Minorités linguistiques et société, 2024)
Dans cet article, nous présentons une synthèse de plusieurs analyses récentes réalisées par notre groupe de recherche à partir de données administratives de santé pour mesurer la qualité et la sécurité des services de santé offerts aux francophones et allophones en Ontario, Canada. Les résultats de nos analyses démontrent que les Ontariennes et les Ontariens qui reçoivent des soins dans leur principale langue d’usage ont généralement de meilleurs résultats cliniques comparés à ceux qui reçoivent des soins dans une langue autre que leur principale langue d’usage. Ceci suggère que la qualité et la sécurité des soins offerts aux patients et aux patientes en situation de discordance linguistique pourraient être améliorées par le pairage de professionnel-patient parlant la même langue, par exemple, en référant un patient à un médecin qui parle la langue du patient, ou en s’assurant que les francophones ont accès aux services en français en milieux désignés en Ontario en vertu de la Loi sur les services en français et que les allophones puissent bénéficier de davantage de services d’interprétariat. Mots-clés : allophones, données administratives de santé, francophones, minorités de langue officielle, minorités linguistiques, qualité et sécurité des soins de santé

Impact of patient–family physician language concordance on healthcare utilisation and mortality: A retrospective cohort study of home care recipients in Ontario, Canada. - Reaume, Michael; Batista, Ricardo; Sucha, Ewa; Pugliese, Michael; Roberts, Rhiannon; Rhodes, Emily; Seale, Emily; Kendall, Claire. E.; Bjerre, Lise; Bouchard, Louise; Johnson, Sharon; Sood, Manish; et al. (BMJ Public Health, 2024)
Introduction As the world’s linguistic diversity continues to increase at an unprecedented rate, a growing proportion of patients will be at risk of experiencing language barriers in primary care settings. We sought to examine whether patient–family physician language concordance in a primary care setting is associated with lower rates of hospital-based healthcare utilisation and mortality. Methods We conducted a population-based retrospective cohort study of 497 227 home care recipients living in Ontario, Canada. Patient language was obtained from home care assessments while physician language was obtained from the College of Physicians and Surgeons of Ontario. We defined primary care as language concordant when patients and their rostered family physicians shared a mutually intelligible language, and we defined all other primary care as language discordant. The primary outcomes were Emergency Department (ED) visits, hospitalisations and death within 1 year of index home care assessment. Results Compared with non-English, non-French speakers who received language-discordant primary care, those who received language-concordant primary care experienced fewer ED visits (53.1% vs 57.5%; p<0.01), fewer hospitalisations (35.0% vs 37.6%; p<0.01) and less mortality (14.4% vs 16.6%; p<0.01) during the study period. In multivariable regression analyses, non-English, non-French speakers had lower risks of ED visits (adjusted hazard ratio [aHR] 0.91, 95% CI 0.88 to 0.94), hospitalisations (aHR 0.94, 95% CI 0.90 to 0.98) and death (aHR 0.87, 95% CI 0.82 to 0.93) when they received language-concordant primary care. For francophones, the risk of experiencing an ED visit, a hospitalisation or death was not impacted by the language of their family physician. Conclusions Patient–family physician language concordance is associated with a lower risk of adverse outcomes in non-English and non-French speakers. Optimising the delivery of language-concordant care could potentially result in significant decreases in the use of acute healthcare services and mortality at the population level.

The impact of hospital language on the rate of in-hospital harm. A retrospective cohort study of home care recipients in Ontario, Canada - Reaume, Michael; Batista, Ricardo; Talarico, Robert; Rhodes, Emily; Guerin, Eva; Carson, Sarah; Prud’homme, Denis; Tanuseputro, Peter (BMC Health Services Research, 2020)
Background Patients who live in minority language situations are generally more likely to experience poor health outcomes, including harmful events. The delivery of healthcare services in a language-concordant environment has been shown to mitigate the risk of poor health outcomes related to chronic disease management in primary care. However, data assessing the impact of language-concordance on the risk of in-hospital harm are lacking. We conducted a population-based study to determine whether admission to a language-discordant hospital is a risk factor for in-hospital harm. Methods We used linked administrative health records to establish a retrospective cohort of home care recipients (from 2007 to 2015) who were admitted to a hospital in Eastern or North-Eastern Ontario, Canada. Patient language (obtained from home care assessments) was coded as English (Anglophone group), French (Francophone group), or other (Allophone group); hospital language (English or bilingual) was obtained using language designation status according to the French Language Services Act. We identified in-hospital harmful events using the Hospital Harm Indicator developed by the Canadian Institute for Health Information. Results The proportion of hospitalizations with at least 1 harmful event was greater for Allophones (7.63%) than for Anglophones (6.29%, p <  0.001) and Francophones (6.15%, p <  0.001). Overall, Allophones admitted to hospitals required by law to provide services in both French and English (bilingual hospitals) had the highest rate of harm (9.16%), while Francophones admitted to these same hospitals had the lowest rate of harm (5.93%). In the unadjusted analysis, Francophones were less likely to experience harm in bilingual hospitals than in hospitals that were not required by law to provide services in French (English-speaking hospitals) (RR = 0.88, p = 0.048); the opposite was true for Anglophones and Allophones, who were more likely to experience harm in bilingual hospitals (RR = 1.17, p <  0.001 and RR = 1.41, p <  0.001, respectively). The risk of harm was not significant in the adjusted analysis. Conclusions Home care recipients residing in Eastern and North-Eastern Ontario were more likely to experience harm in language-discordant hospitals, but the risk of harm did not persist after adjusting for confounding variables.

The impact of patient-facility language discordance on potentially inappropriate prescribing of antipsychotics in long-term care home in Ontario, Canada: A retrospective population health cohort study - Reaume, Michael; Peixoto, Cayden; Pugliese, Michael; Tanuseputro, Peter; Batista, Ricardo; Kendall, Claire. E.; Landry, Josette-Renée; Prud’homme, Denis; Chomienne, Marie-Hélène; Farrell, Barbara; Bjerre, Lise M. (BMC Geriatrics, 2024)
Background Appropriate use of medication is a key indicator of the quality of care provided in long-term care (LTC). The objective of this study was to determine whether resident-facility language concordance/discordance is associated with the odds of potentially inappropriate prescribing of antipsychotics (PIP-AP) in LTC. Methods We conducted a population-based, retrospective cohort study of LTC residents in Ontario, Canada from 2010 to 2019. We obtained resident language from standardized resident assessments, and derived facility language by determining the proportion of residents belonging to each linguistic group within individual LTC homes. Using linked administrative databases, we identified all instances of PIP-AP during a 1-year follow-up period. PIP-AP was defined using the STOPP-START criteria, which have previously been shown to predict adverse clinical events such as emergency department (ED) visits and hospitalizations. The association between linguistic factors and PIP-AP was assessed using adjusted multivariable logistic regression analysis. Results We identified 198,729 LTC residents consisting of 162,814 Anglophones (81.9%), 6,230 Francophones (3.1%), and 29,685 Allophones (14.9%). The odds of PIP-AP of were higher for both Francophones (aOR 1.15, 95% CI 1.08–1.23) and Allophones (aOR 1.11, 95% CI 1.08–1.15) when compared to Anglophones. When compared to English LTC homes, French LTC homes had greater odds of PIP-AP (aOR 1.12, 95% CI 1.05–1.20), while Allophone homes had lower odds of PIP-AP (aOR 0.82, 95% CI 0.77–0.86). Residents living in language-discordant LTC homes had higher odds of PIP-AP when compared to LTC residents living in language-concordant LTC homes (aOR 1.07, 95% CI 1.04–1.10). Conclusion This study identified linguistic factors related to the odds of PIP-AP in LTC, suggesting that the linguistic environment may have an impact on the quality of care provided to residents.

Cognitive health initiative for Francophone seniors in the GTA - Reflet Salvéo; Entité 4 (Options fo Service Models, 2017)

Rapport sur l’accès aux soins de longue durée en français dans la région de Champlain. Sommaire - Réseau des services de santé en français de l’Est de l’Ontario (2020)

Boîte à outils virtuelle de soins culturellement adaptés pour les francophones dans les foyers de SLD - Réseau du mieux-être francophone du Nord de l’Ontario (2022)

État des lieux pour le secteur des soins à domicile et en milieu communautiare dans le nord de l'Ontario - Réseau du mieux-être francophone du Nord de l'Ontario (2025)
Le Réseau a entrepris le travail de recenser les capacités actuelles du secteur des soins à domicile et en milieu communautaire dans le Nord de l’Ontario, et ce, afin de mieux appuyer les organismes de soins de santé et ainsi renforcer les capacités du secteur. En effet, cette étude permettra au Réseau de connaître les capacités actuelles en termes de professionnels de la santé qui parlent le français dans le Nord de l’Ontario, puis d’identifier les domaines et les régions où les disparités sont plus importantes. Ce rapport pourra servir de guide envers l’établissement des priorités et de stratégies régionales en matière de services en français pour le secteur des soins à domicile et en milieu communautaire.

Recommandations de l’étude de besoins sur les foyers de soins de longue durée du Nord de l’Ontario - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)

Recommendations from the Northern Ontario Long-Term Care Homes Needs Study - Réseau du mieux-être francophone du Nord de l’Ontario (Réseau du mieux-être francophone du Nord de l’Ontario, 2022)

Guide de planification et de prestation des soins de longue durée en français. Leçons tirées du pavillon Omer Deslauriers de Bendale Acres et d'autres services de santé en français pour aînés au Canada - Réseau franco-santé du Sud de l’Ontario (2017)

The impact of dementia and language on hospitalizations: A retrospective cohort of long-term care residents - Riad, Karine; Webber, Colleen; Batista, Ricardo; Reaume, Michael; Rhodes, Emily; Knight, Braden; Prud’homme, Denis; Tanuseputro, Peter (BMC Geriatrics, 2020)
Background Hospitalizations carry considerable risks for frail, elderly patients; this is especially true for patients with dementia, who are more likely to experience delirium, falls, functional decline, iatrogenic complications, and infections when compared to their peers without dementia. Since up to two thirds of patients in long-term care (LTC) facilities have dementia, there is interest in identifying factors associated with transitions from LTC facilities to hospitals. The purpose of this study was to investigate the association between dementia status and incidence of hospitalization among residents in LTC facilities in Ontario, Canada, and to determine whether this association is modified by linguistic factors. Methods We used linked administrative databases to establish a prevalent cohort of 81,188 residents in 628 LTC facilities from April 1st 2014 to March 31, 2017. Diagnoses of dementia were identified with a previously validated algorithm; all other patient characteristics were obtained from in-person assessments. Residents’ primary language was coded as English or French; facility language (English or French) was determined using language designation status according to the French Language Services Act. We identified all hospitalizations within 3 months of the first assessment performed after April 1st 2014. We performed multivariate logistic regression analyses to determine the impact of dementia and resident language on the incidence of hospitalization; we also considered interactions between dementia and both resident language and resident-facility language discordance. Results The odds of hospitalization were 39% lower for residents with dementia compared to residents without dementia (OR 0.61, 95% CI 0.57–0.65). Francophones had lower odds of hospitalization than Anglophones, but this difference was not statistically significant (OR 0.91, 95% CI 0.81–1.03). However, Francophones without dementia were significantly less likely to be hospitalized compared to Anglophones without dementia (OR 0.71, 95% CI 0.53–0.94). Resident-facility language discordance did not significantly affect hospitalizations. Conclusions Residents in LTC facilities were generally less likely to be hospitalized if they had dementia, or if their primary language was French and they did not have dementia. These findings could be explained by differences in end-of-life care goals; however, they could also be the result of poor patient-provider communication.

Structural facilitators and barriers to access to and continuity of French-language healthcare and social services in Ontario’s Champlain region - Savard, Jacinthe; Bigney, Kte; Kubina, Lucy-Ann; Savard, Sébastien; Drolet, Marie (Healthcare Policy, 2020)
Purpose: The purpose of this article is to examine access to and continuity of French-language healthcare and social services in Ontario's Champlain region through an analytical framework that incorporates people seeking care, their caregivers and the linguistic component of care into a health and social service system bounded by community, organizational, political and symbolic structures. Methods: Experiences of French-speaking seniors seeking care and those of health and social service providers and managers from two qualitative exploratory studies are used to describe trajectories through the system. Results: Participants exposed how, together with community vitality, issues within each of the system's symbolic, political or regulatory and organizational structures influence these trajectories. Conclusions: To meet the needs of francophone seniors, additional work is needed to increase French-language services coordination within the organizational, regulatory and policy structures of the health and social service system.

Évaluation de Marche vers le futur, un programme novateur de prévention des chutes offert par videoconference - Savard, Jacinthe; Labossière, Sophie; Cardinal, Dominique; Pinet, Bernard; Borris, Caroline (La Revue canadienne du vieillissement, 2018)
Several fall prevention programs have been implemented to reduce falls among seniors. In some rural areas or in French-speaking minority communities, the availability of such programs is limited. The objectives of this paper are to: (a) describe the Fall Prevention Program Marche vers le futur, offered in French, by videoconference; and (b) present the results of the evaluation of the program objectives. Results demonstrate that participants have improved their physical abilities, gained knowledge, adopted new behaviors and lifestyle habits. In short, Marche vers le futur reduces fall risk factors in a manner equal or superior to other programs. Marche vers le futur has made possible the provision of services in French in communities where availability of French-language resources is very limited, therefore fostering equity in access to health services.

Strategies to improve French language health and social service continuity for seniors in Ontario and Manitoba - Savard, Jacinthe; Savard, Sébastien; de Moissac, Danielle; Giasson, Florette; Kubina, Lucy-Ann (Linguistic Minorities and Society, 2021)
Access to health and social services in one’s official language of choice is an important component of quality and safety of care for seniors. Access can be fragmented, even in the context of legislation guaranteeing the right to receive such services, and in areas with a higher proportion of bilingual providers. Using a community-based participatory approach, we identified mechanisms promoting or impeding the clinical integration of health and social French language services intended for seniors living in two Canadian Francophone minority communities. Thirteen recommendations highlight the possibility for new initiatives to promote a continuum of French language health and social services in a minority context, involving collaboration among a variety of actors at all levels of our analytical framework: service trajectory (providers); francophone communities; organizational; political and regulatory; and symbolic (values) structures. Keywords: seniors, linguistic minorities, service integration, health and social services, continuity of care

Practice # 3: The Pavillon Omer Deslauriers: A Francophone Unit at Bendale Acres (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 10 : Les points de service satellites (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 12 : Les Lunchs-causeries au Centre de services communautaires Vanier (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 13 : Une infirmière de Santé publique dans un centre de services communautaires qui assure l’aiguillage des aînés (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 14 : Les Foires d’information de la Fédération des aînés et des retraités francophones de l’Ontario (FARFO) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2021)

Pratique # 9 : Les Soins primaires communautaires pour aînés (Primary Care Outreach to Seniors) (Ontario) - Savard, Jacinthe; Savard, Sébastien; van Kemenade, Solange; Benoît, Josée; Buhay, Corrina; Youbi, Sara; Kubina, Lucy-Ann (2019)

Recruitment and retention of bilingual health and social service professionals in Francophone minority communities in Winnipeg and Ottawa - Savard, Sébastien; de Moissac, Danielle; Benoît, Josée; Ba, Halimatou; Zellama, F.; Giasson, Florette; Drolet, Marie (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Le recrutement et la rétention d’intervenants en santé et services sociaux bilingues en situation francophone minoritaire à Winnipeg et à Ottawa - Savard, Sébastien; de Moissac, Danielle; Benoît, Josée; Ba, Halimatou; Zellama, Faïçal; Giasson, Florette; Drolet, Marie (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
La difficulté à recruter des professionnels en mesure d’intervenir dans les deux langues officielles a été mentionnée comme une des causes les plus importantes du manque d’accès à des services sociaux et de santé en français pour les personnes âgées francophones en situation minoritaire. Ce chapitre présente les résultats d’une recherche réalisée auprès de 55 intervenants, rencontrés dans six groupes de discussion et travaillant dans des organisations bilingues dans deux régions, soit Winnipeg au Manitoba et Ottawa en Ontario. Nous voulions connaître les facteurs ayant incité ces intervenants à vouloir travailler dans des organisations bilingues et ceux favorisant leur rétention dans les organismes où ils travaillent. Les résultats démontrent que la volonté de contribuer au mieux-être des francophones et la possibilité d’obtenir des postes stables offrant des conditions de travail intéressantes font partie des facteurs de recrutement les plus importants. La qualité du climat de travail et la possibilité de travailler dans un milieu caractérisé par la diversité sont des facteurs de rétention mentionnés régulièrement par les participants à l’étude. Une meilleure reconnaissance du fardeau supplémentaire associé au fait de travailler dans les deux langues et le recrutement de cadres bilingues font partie de recommandations permettant de faciliter le recrutement et la rétention de personnel bilingue. Mots-clés : recrutement et rétention, intervenants services sociaux et de santé, francophones en situation minoritaire.

L’accès aux services en français, de la connaissance des défis à l’accompagnement des organisations vers le changement. - Savard, Sébastien; Savard, Jacinthe; Sauvé-Schenk, Katrine; van Kemenade, Solange; Benoît, Josée (Minorités linguistiques et société, 2024)
Depuis 2011, le Groupe de recherche sur la formation et les pratiques en santé et service social en contexte francophone minoritaire (GReFoPS) cherche à mieux comprendre les facilitateurs et les obstacles à l’offre de services en français dans un contexte linguistique minoritaire au Canada. Dans cet article, les auteurs présentent un bilan de près de 12 ans de recherche sur le sujet, en décrivant les facteurs individuels et organisationnels qui influencent l’offre de services en français. Les résultats de ces études ont mis en lumière quelques mécanismes organisationnels ou interorganisationnels qui ont permis l’émergence de pratiques novatrices pour améliorer l’offre de services en français dans les services communautaires et institutionnels. On y décrit également des outils créés pour aider les gestionnaires de ces services à identifier des mesures et des mécanismes pouvant répondre aux besoins des usagers francophones en situation minoritaire. Mots-clés : accès, services sociaux et de santé, francophones, contexte minoritaire, Canada

Le vieillissement francophone en contexte minoritaire. Défis et opportunités - Siméon, Frantz; Couturier, Yves (Reflets, 2021)

Enjeux et complexité de la démence en milieu rural francophone : regards sur les réalités familiales [mémoire de maîtrise, Université d'Ottawa] - Sullivan, Cassidy (Université d'Ottawa, 2020)
Les personnes aînées se retrouvent parmi les groupes les plus susceptibles d’être diagnostiqués d’une maladie cognitive, telle qu’une démence. La réception du diagnostic est un événement bouleversant pour toutes les personnes impliquées, et plus particulièrement pour les familles. Dans la région d’Ottawa, il existe une variété de ressources pour soutenir les personnes atteintes d’une démence ainsi que leurs proches. Or, la littérature disponible indique que les personnes francophones vivant dans un milieu rural ne vivent pas la même réalité (Forgues, Doucet et Guignard (2011). Bien que les impacts de la démence sur les relations familiales pourraient varier d’un endroit à un autre, l’emplacement et la disponibilité des services francophones jouent également un rôle important dans le parcours de ces personnes. Ces facteurs nous invitent à poser la question suivante : Quels sont les impacts de la démence sur la dynamique familiale et l’accès aux services francophones des personnes vivant dans un milieu rural ? À partir de la perspective d’intervenantes sociales, l’étude a permis : 1) d’explorer les réalités et enjeux vécus par les familles lors de la réception d’un diagnostic de démence, comme la maladie d’Alzheimer, chez un proche âgé vivant dans un contexte rural francophone ; 2) d’examiner les défis d’accès aux services rencontrés par les aidants familiaux, et finalement ; 3) de comprendre les réalités des familles lors de la progression de la maladie. Cette recherche a été menée dans les Comtés unis de Prescott-Russell, une région bilingue de l’est de l’Ontario. Dans cette étude, nous avons identifiés le vécu des familles suite à la réception d’un diagnostic de démence, ainsi que les ressources disponibles pour les personnes de cette région qui sont touchées par la maladie. En ce qui trait au cadre conceptuelle et théorique choisi pour cette étude, nous avons optés pour l’épreuve relationnelle et l’approche écosystémique pour analyser nos thèmes. Sur le plan méthodologique et en se basant sur des entrevues semi-dirigées, cette étude a nécessité la participation de trois intervenantes sociales œuvrant auprès des familles ayant un proche atteint d’une démence, et ce, dans la région de Prescott-Russell. Il ressort principalement des résultats de cette étude que les enjeux observés par les intervenantes sur la gestion de la démence en milieu rural et l’accès aux services sont lié à la navigation entre les services, l’éducation sur la démence et l’optimisation des services de soutien. Ces dernières constatent des points à améliorer en ce qui concerne le discours social sur le vieillissement ainsi que le manque de financement pour l’augmentation de la visibilité et de l’accessibilité des services francophones. Mots clés : Personne aînée, maladie d’Alzheimer, ruralité, francophonie, accessibilité, services adaptés, dynamique familiale

L’impact d’un programme éducatif sur la qualité de vie de personnes aînées autonomes et hypertendues en milieu francophone minoritaire [thèse de maîtrise, Université d'Ottawa] - Taillon, Myriam (2016)
L’hypertension artérielle est une maladie chronique qui affecte près de 50 % des personnes de plus de 65 ans au Canada et de façon disproportionnelle, les communautés en situation minoritaire linguistique. L’objectif du projet était de sensibiliser des personnes de 65 ans et plus, hypertendues, en milieu francophone minoritaire aux facteurs de risque de l’hypertension par des ateliers éducatifs. L’impact de ces ateliers a été mesuré par un questionnaire sur la qualité de vie et des groupes de discussion. Il y a eu 34 participants. Les questionnaires ont révélé une amélioration dans les dimensions physique et mentale de la santé des participants (p < 0,001). Les groupes de discussion ont démontré que les participants comprenaient mieux la maladie et avaient modifié certains comportements. Les ateliers ont été reconnus comme très positifs par les participants. En conclusion, ce programme éducatif de 3 mois est efficace, faisable et apprécié chez cette population. Mots-clés hypertension artérielle, haute pression, francophone en situation linguistique minoritaire, personnes aînées, prise en charge, programme éducatif

Differences between the francophone and Anglophone ethno-linguistic groups in the Ontario home care setting [master's thesis, Lakehead University] - Thériault, Eric. R. (2009)

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Expériences en foyers de soins de longue durée et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Benoît, Josée; Bouchard, Louise; Sauvé-Schenk, Katrine; Savard, Jacinthe (Chaire de recherche de l’Université d’Ottawa et de l’Institut du savoir Montfort sur la santé des francophones de l’Ontario (2019-2024), Université d’Ottawa, 2025)
L’étude rapportée dans ce rapport de synthèse visait à cerner la disponibilité de services en français dans les FSLD, leur accès, ainsi que l’impact de barrières linguistiques sur la santé et le bien-être, la qualité et la sécurité de soins à partir des perspectives des gestionnaires, des intervenant·es et des personnes résidant dans un FSLD ou de leur proche aidant·e. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des foyers, qu’ils soient à caractère francophone, désignés, identifiés ou non identifiés. Ce rapport de synthèse en décrit les principaux constats, accompagnés de quelques citations de participants.